Factors Influencing the Use of Prenatal Care: A Systematic Review (Mashhad University of Medical Sciences, 2016)
Background & aim: Prenatal care is a key strategy for achieving public health goals, primary healthcare objectives, and the Millennium Development Goals. The aim of this study was to investigate the factors influencing the use of prenatal care services in order to design suitable interventions and promote the use of these services. Methods:In this systematic quantitative literature review, studies published in years 2010-2014 were evaluated. For this purpose, two international electronic databases, i.e., Scopus and PubMed, were explored to find English-language articles by using relevant keywords; moreover, the reference lists of the articles were hand-searched. We reviewed all cross-sectional and prospective studies, which focused on factors associated with the use of prenatal care services within the specified period of time. Results: In total, 17 relevant articles were included in our review. The results showed that late initiation and inadequate use of prenatal care services are independently associated with multiple variables, including demographic characteristics, socioeconomic factors, predisposing cultural and religious factors, social support, factors related to healthcare providers, women's awareness and attitude, unintended pregnancy, high-risk medical or obstetric history, and health behaviors. Conclusion: Based on the literature review, proper use of prenatal care cannot be achieved merely by establishing healthcare centers. Utilization of maternal health services may be achieved and improved via developing socioeconomic factors and addressing patients' basic needs including education and financial independence.